Cooperative Supramolecular Polymerization of Fluorescent Platinum Acetylides for Optical Waveguide Applications. (29th August 2017) - Wang, Xiao; Han, Yifei; Liu, Yingying; Zou, Gang; Gao, Zhao; Wang, Feng
Abstract: One‐dimensional organic structures with well‐oriented π‐aggregation, strong emission, and ease of processability are desirable for optoelectronic waveguiding devices. Herein, a strategy is developed to attain this objective by self‐assembling platinum(II) acetylides into fluorescent supramolecular polymers via cooperative mechanism. The resulting high‐molecular‐weight supramolecular polymers are capable of forming electrospun microfibers with uniform geometry and smooth surface, which enable light propagation with extremely low scattering loss (0.008 dB μm −1 ). With the elaborate combination of bottom‐up supramolecular polymerization and top‐down electrospinning techniques, this work offers a novel and versatile avenue toward high‐performance optical waveguiding materials. Abstract : Ein natürliche Vorgänge imitierender Keimbildungs‐Verlängerungs‐Mechanismus überführt Platinacetylide in hochmolekulare supramolekulare Polymere, was die kostengünstige Erzeugung einheitlicher fluoreszierender 1D‐Mikrofasern ermöglicht. Eine solche Kombination aus Bottom‐up‐Selbstorganisation und Top‐down‐Elektrospinnen bietet einen effizienten Zugang zu optischen Hochleistungs‐Wellenleitermaterialien.